Human nature and its destiny in Indian thought with special reference to the Advaita of Sankara - Desai, J.G. (Nidān, 1994)
Indian culture, like the other cultures of the world, has always sought to understand the conditions and meaning of the struggle for existence in a universe, which is by all rational accounts, a mystery, Indian thought, therefore, has been perennially exercised over the enigmatic character of human life and the world. This paper is a brief attempt to show how the thought traditions of India, especially the metaphysical perspective of Sankara's Advaita Vedclnta, sought to address the problem of human nature and its destiny, The ideas seminal to Sailkara's Advaita and to the Upani~ads, from which he derived the essentials of his theory, have a long philosophic ancestry to be traced to the hymns of the IJgVeda, one of which, at least the Niisadiya Sukta. has monistic import.